Socioemotional Well-Being as a Predictor of Mental Health among Malaysian University Students: Implications for Southeast Asian Higher Education - Marini Abd Razak; Aishah Hanim Abd Karim; Hamidah Mohamad (Advances in Psychological Sciences and Applications, 2026)
Mental health challenges among university students have become a pressing concern, particularly within higher education environments characterised by academic demands, social transitions, and sociocultural pressures. This study investigates the predictive role of socioemotional well-being (SEWB) in shaping mental health outcomes among university students in Malaysia. A quantitative, cross-sectional design was employed, involving 442 undergraduate students from higher education institutions. Socioemotional well-being was assessed using a multidimensional framework encompassing emotional regulation and social functioning, while mental health was measured using the Mental Health Inventory (MHI-38). Data were analysed using descriptive statistics, Pearson correlation, and multiple regression analysis. The findings revealed a strong and significant positive relationship between SEWB and mental health (r = 0.70, p < 0.05). Regression analysis further demonstrated that SEWB is a significant predictor of mental health (β = 0.70, p < 0.05), explaining 48.9% of the variance (R² = 0.489), with the model achieving statistical significance (F = 210.403, p < 0.05). These findings underscore the critical role of socioemotional well-being as a key determinant of student mental health and highlight its potential as a strategic focus for intervention in higher education across Southeast Asia.